An Easy and Multigram-Scale Synthesis of Pillar[5]quinone by the Hypervalent Iodine Oxidation of 1,4-Dimethoxypillar[5]arene - Shivakumar, Kilingaru I.; Sanjayan, Gangadhar J. (Synthesis, 2013)
Pillar[5]quinone (P[5]Q), a potential molecule for anion recognition and supramolecular host-guest chemistry, has not as yet been used for practical purposes, presumably due to the synthetic difficulties in obtaining it in large amounts. Herein, we reveal an easy-to-operate and chromatography-free synthetic strategy that can furnish P[5]Q on a multigram scale; its success relies on the utility of hypervalent iodine, generated in situ from Oxone/iodobenzene, as an efficient oxidant. Pillar[5]quinone was obtained in multigram quantities by oxidation of 1,4-dimethoxypillar[5]arene with Oxone/iodobenzene and simple purification by crystallization from 1,1,2,2-tetrachloroethane, thus opening up the opportunity to explore the properties of this interesting macrocyclic quinone.
Keywords: supramolecular chemistry; macromolecules; pillararenes; hypervalent iodine oxidation